Impacto Del Covid En El Desempeño Organizacional Y Financiero De La Industria Hotelera Y Situación Actual En Escenario De Postpandemia: Caso De Estudio Hotel Génesis. - Novoa Carrasco, Carmen Elena (Universidad Antonio Nariño, 2023)
This paper presents an analysis of the results of the observation and interviews that identify the organizational status and financial indicators that measure liquidity, profitability, indebtedness and management, of the study case: Génesis Hotel, in order to assess the COVID impact on performance. financial and organizational in the hotel industry, for the study quantitative and qualitative information is taken from the year 2017 to 2021